OBSERVACIONES ACERCA DEL DESARROLLO Y CARACTERES MORFOLOGICOS DE TRIATOMA PICTURATA USINGER - ISLAS S, FEDERICO (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1941)
Some spp of Hydroides from the Pacific coast of Mexico are described H californicus and H brachyacantha from Acapulco and Mazatlan; H ochotereana, H recurvispina, and H glandiferum from Acapulco
ANS INST BIOL
Keywords: OBSERVACIONES, DESARROLLO, CARACTERES MORFOLOGICOS, TRIATOMA PICTURATA USINGER; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; INSECTOS